The social life of the Samson Saga in Israeli religious Zionist rabbinic discourse. Issue 2 (3rd April 2018) - Stern, Nehemia
Abstract: This article will explore how different contemporary groups of Israeli religious Zionists read and relate to the Biblical tales of Samson. Using current religious Zionist discourse (Bible lessons, newspaper articles and written opinion pieces) authored or delivered by leading rabbinic figures, this article will demonstrate how contemporary interpretations of the 'Samson Saga' (Judges 13–16) are used as a medium through which contemporary religious Zionists in Israel and the West Bank contest the meanings of political sovereignty, violence and personal ethics. More broadly, this article will argue that a focus on how sacred texts are interpreted, debated and contested in social contexts (or the 'social life' of a text) can offer scholars a thicker and more nuanced window into the varied ways in which religious nationalists grapple with competing political visions and desires.